1986
DOI: 10.1093/oxfordjournals.eurheartj.a062033
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide assessment of a normal left ventricular response to exercise in patients without evidence of heart disease

Abstract: The aim of this study was to define normal left ventricular performance at rest and during supine bicycle exercise with equilibrium radionuclide ventriculography in a normal population other than young healthy volunteers. Thirty-one patients (mean age 45 years +/- 9 SD) with chest pain of varying origin and no evidence of heart disease proven by means of noninvasive and invasive techniques were studied. Left ventricular ejection fraction (LVEF) at rest averaged 0.64 +/- 0.07 SD and increased with peak exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
3
4
0
1
Order By: Relevance
“…LV and RV EDV did not increase during exercise; RV EDV actually decreased slightly at the highest Hence, in the absence of an increase in EDV, the improvement in SV is most likely a reflection of increased contractility rather than a result of the FrankStarling mechanism and more favorable muscle fiber stretch. These results are in keeping with previous reports of studies using radionuclide (17)(18)(19) and MRI (7) techniques and describe the physiological response to exercise seen in young adults (20). Therefore, we believe that the described exercise protocol represents effective and physiological modality for cardiac stress testing.…”
Section: Physiological Response To Exercisesupporting
confidence: 91%
“…LV and RV EDV did not increase during exercise; RV EDV actually decreased slightly at the highest Hence, in the absence of an increase in EDV, the improvement in SV is most likely a reflection of increased contractility rather than a result of the FrankStarling mechanism and more favorable muscle fiber stretch. These results are in keeping with previous reports of studies using radionuclide (17)(18)(19) and MRI (7) techniques and describe the physiological response to exercise seen in young adults (20). Therefore, we believe that the described exercise protocol represents effective and physiological modality for cardiac stress testing.…”
Section: Physiological Response To Exercisesupporting
confidence: 91%
“…This was also noted by Schoen et al [14] and Manyari et al [16] in studies of normal subjects undergoing supine bicycle exercise. However, Steingart et al [10] reported an increase in diastolic volume in the early stages of both supine and upright exericse, with no significant changes in the later stages.…”
Section: Ejection Fraction (Lvef)supporting
confidence: 70%
“…This increase in EF, although not marked, was significant in our athletes. The moderate increase in EF can be ex plained by the observation [6] that EF values at rest in our trained athletes were just above those observed in normal subjects [7], while other studies [8,9] demon strated a similarity in the resting values between normal untrained subjects and athletes. Moreover, an increase of greater than 5 % in EF values during exercise in nor mal subjects is seldom not seen, thus suggesting that these limits are an artificial and arbitrary line of discrim ination between normal and abnormal responses, put ting in doubt its specificity [10,11].…”
Section: Discussionmentioning
confidence: 64%
“…At intermediate exercise workload E-I, a slight in crease in EF was induced which tended to increase pro gressively [5,6] towards E-II and during RP. This increase in EF, although not marked, was significant in our athletes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation